ATP in the locus coeruleus as a modulator of cardiorespiratory control in unanaesthetized male rats - Biancardi, Vivian [UNESP]; Bicego, Kenia Cardoso [UNESP]; Gargaglioni, Luciane H. [UNESP] (Wiley-Blackwell, 2014)
Locus coeruleus (LC) noradrenergic neurons are chemosensitive to CO2 and pH in mammals and amphibians and are involved in the CO2-related drive to breathe. Purinergic neuromodulation in the LC is of particular interest because ATP acts as a neuromodulator in brainstem regions involved in cardiovascular and respiratory regulation, such as the LC. ATP acting on LC P2 receptors influences the release of noradrenaline. Thus, the goal of the present study was to investigate the role of LC purinergic neuromodulation of ventilatory and cardiovascular responses in normocapnic and hypercapnic conditions in unanaesthetized male Wistar rats. We assessed the purinergic modulation of cardiorespiratory systems by microinjecting an ATP P2X receptor agonist [,-methylene ATP (,-meATP), 0.5 or 1 nmol in 40 nl] and two non-selective P2 receptor antagonists [pyridoxalphosphate-6-azophenyl-2,4-disulfonic acid (PPADS), 0.5 or 1 nmol in 40 nl; and suramin, 1 nmol in 40 nl] into the LC. Pulmonary ventilation (measured by plethysmography), mean arterial pressure (MAP) and heart rate (HR) were determined before and after unilateral microinjection (40 nl) of ,-meATP, PPADS, suramin or 0.9% saline (vehicle) into the LC. These measurements were made during a 60 min exposure to normocapnic conditions or a 30 min exposure to 7% CO2. Subsequently, animals undergoing pharmacological treatment were subjected to a 30 min exposure to normocapnic conditions as a recovery period. In normocapnic conditions, ,-meATP did not affect any parameter, whereas PPADS decreased respiratory frequency and increased MAP and HR. Suramin increased MAP and HR but did not change ventilation. Moreover, hypercapnic conditions induced an increase in ventilation and a decrease in HR in all groups. In hypercapnic conditions, ,-meATP increased ventilation but did not change cardiovascular parameters, whereas PPADS increased MAP but did not alter ventilation, and suramin increased both ventilation and MAP. Thus, our data suggest that purinergic signalling, specifically through P2 receptors, in the LC plays an important role in cardiorespiratory control in normocapnic and hypercapnic conditions in unanaesthetized rats.